Menelaah Tipologi dan Karakteristik Kepemimpinan Kepala Sekolah di Lembaga Pendidikan Indonesia(Studi Literatur Kepemimpinan) - Dinda Aprilia Putri; Adil Mubarok; Nora Eka Putri; Padrison Padrison (Indo Publishing, 2026)
The progress of educational institutions in Indonesia is largely determined by the principal or school leader. This article examines the typology and characteristics of principal leadership in Indonesian educational institutions using a literature review analysis. Based on five research findings, it was found that educational institutions in Indonesia implement various leadership typologies: mixed (democratic-paternalistic), transformational, religio-paternalistic, socialistic, and laissez-faire. Furthermore, leadership characteristics depend on or are related to the typology implemented by each principal within the educational institution. For example, if the principal's leadership typology applies a transformative type, then the leadership characteristics tend to be able to work together, communicate with all parties, have a varied identity and leadership style and are able to accept suggestions and criticism from others.